La Mielogénesis : acción concertada de la transferrina y la hormona tiroideas - Marziali, Leandro Nazareno (2016)
In the central nervous system (CNS), Transferrin (Tf) and Thyroid Hormones (THs) promoted oligodendrocyte (OLG) maturation and myelination. Results from our laboratory suggested that Tf and THs could act together in the regulation of the above mentioned processes, given that THs modulated Tf expression and Tf might have effects on THs receptor alpha (TR?). In order to elucidate this potential interaction mechanism, we performed some in vivo experiments to test the combined effects of Tf and THs on myelination and on THs receptors (TRs) expression as well. Additionally, we used neural progenitor cells (NPCs) and analyzed the action of both factors acting together or individually on OLG maturation.\nOur in vivo results showed that apoTransferrin (aTf) and THs exerted individual positive effects on myelination. Furthermore, THs regulated Tf expression during the first two weeks of life and there was an interaction between both factors involving TRs since THs regulated TR? expression and Tf modulated TR? expression.\nThe in vitro experiments revealed that when Tf expression is knocked down OLG maturation was limited. Under these circumstances, THs partially promoted OLG maturation and when TR? was blocked, aTf was able to partially support OLG maturation. Tf knock down decreased TR? expression while aTf administration induced the contrary. At the same time, the treatment of CPNs with THs induced the increase of TR? expression and a premature increase of Tf expression which was abolished by blocking TR?.\nThese findings indicated that the combined actions of Tf and THs are required in order to achieve a proper OLG maturation and myelination; in addition the effects observed are the consequence of the crosstalk between the actions of both factors on OLG maturation. In agreement with this hypothesis, our results demonstrated that THs were capable of regulating Tf expression, which in turns exerted positive effects on OLG maturation and increased TR? expression as part of a feedback circuit, which together with THs effects mediated by TR? ensured the accomplishment of an adequate OLG maturation and myelination.